Analisis Perhitungan Pajak Pertambahan Nilai Pada PT Sinar Pure Internasional Bitung - Lulage, Selci; Afandi , Dhullo; Mintalangi, Syermi S.E (GOING CONCERN : JURNAL RISET AKUNTANSI, 2023)
Taxes are contributions of taxpayers to the State owed by individuals or entities that are coercive under the Law, by not receiving direct compensation and being used for the needs of the State. Value Added Tax is a type of indirect tax which is included as a consumption tax in the country, both consumption of goods and consumption of services. In general, Value Added Tax (VAT) is a tax imposed on the added value of a good or service after going through the production process. In principle, every company performs calculations, deposit and tax reporting in connection with the activities carried out by the company. This research was conducted at PT Sinar Pure Foods International, Bitung City. The purpose of this research is to find out that the calculation of Value Added Tax made by PT Sinar Pure Foods International is in accordance with applicable regulations. The analytical method used in this study is a qualitative descriptive analysis method. Based on the results of the study, it shows that the calculation of Value Added Tax is in accordance with the applicable regulations, namely Law Number 42 of 2009 Keywords: Calculation of Value Added Tax